An intranasally administered IgM protects against antigenically distinct subtypes of influenza A viruses - Ashwin Kumar Ramesh; Jwala Priyadarsini Sivaccumar; Xiaohua Ye; Luona Yang; Hailong Guo; Chen-Ni Chin; Sha Ha; John W. Shiver; William R. Strohl; Yan Xu; Haijuan Du; Tongqing Zhou; et al. (Nature Communications)
Abstract Engineering broadly neutralizing monoclonal antibodies (mAbs) targeting the hemagglutinin (HA) of Influenza A virus (IAV) is a promising approach for intervention of seasonal flu. However, HA plasticity often leads to resistant strains that compromise mAb potency as bivalent IgGs. Here we hypothesize that multimerization of anti-IAV antibodies as IgMs can enhance coverage and neutralization potency. Here, we construct 18 IgM antibodies from known broadly neutralizing IgGs targeting different IAV HA epitopes and evaluate their breadth and potency of neutralization against distinct H1N1 and H3N2 IAVs. The IgM version of receptor binding site-specific IgG F045-092 shows increased breadth and antiviral potency compared to its parental IgG. Engineered IgM molecules overcome IAV strain resistance by expanded avidity, providing potent neutralization in vitro at sub-nanomolar ranges while retaining parental IgG specificity. Intranasal delivery of engineered IgM-F045-092 in female mice demonstrates efficient bio-retention in nasal cavities and lungs, offering protection against lethal doses of H1N1 and H3N2 IAV when administered prophylactically. Optimal epitope selection, trans-crosslinking, decavalent avidity, and intranasal administration contribute to the broader protection and potency of engineered IgM antibodies against diverse IAV subtypes.